Adapting Phaëton - Burden, M (2011)
London's opera season of 1746-47 must have seemed strange to the audience at the opera house. Under the direction of an unknown Spanish composer Domingo Terradellas, it consisted of only four operas: the pasticcio Anibale in Capua (a version said to be Terradellas's work), the composer's settings of Mitridate and Bellerofonte, Domenico Paradies' opera Fetonte, and some unspecified theatre dances. The musical and dramatic forms of all the operas were unusual, and their manner of employment suggests an intention by the impresario Francesco Vanneschi to promote opera with a greater integration of the genre's elements. These intentions were to some extent laid out in 'A discourse on the operas, humbly inscrib'd to the Right Honourable the Earl of Middlesex', written by John Lockman (1698-1771), and appended to the published libretto. Lockman, a successful critic and translator, also wrote for the theatre, and his text clearly had the support of Vanneschi, who may have been inspired to commission it on the basis of Lockman's 'Some Reflection on the opera…'; this had appeared as a preface to the 1744 Rosalinda, an opera based Shakespeare's As you like it. Of all the works included in the season, it is the libretto of Fetonte by Vanneschi himself that most closely adheres to the aims so persuasively stated by Lockman. Vanneschi - a difficult, short-tempered, and over-bearing impresario - claimed the role of author repeatedly, a claim which has been re-stated on numerous occasions since. However, this paper argues that the libretto was not, in fact, by him at all, but was based directly on Quinault's tragédie en musique, Phaëton, a text after Ovid's Metamorphoses. Containing the famous chariot machine designed by Jean Berain and set to music by Jean-Baptiste Lully, this great spectacular in a prologue and five acts, was performed at Versailles on 6 January 1683, and was the model for Niccolò Jommelli's last opera for the Duke of Württemberg, written for the newly constructed theatre at Ludwigsburg in 1768. If Vanneschi's authorship is in doubt, then so is the 'revolutionary' nature of the season.